The Enhancement of Verbal Communication Skills for Vocational Students through Project-Based Learning Physics - Nur Fitri Asih; Ellianawati Ellianawati (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2019)
Research has been conducted to train the verbal communication skills of Vocational students through project-based learning. This study aims to train students' verbal communication skills through learning project-based. The research is a pre-experimental design in the form of a one-shot case study. This research was conducted at Diponegoro Vocational High School in the 2018/2019 school year for students in class X TKR 2, totaled 33 students. The instruments used were observation sheets of oral communication and written communication skills, worksheets, and documentation. The Results Showed that the communication skills of Diponegoro Vocational High School students According to indicators of oral communication abilities were Able to express opinions and listen to the opinions of others as much as 61.36%, Able to master the material to be made as presentation material of 59.10%, Able to systematically submit report results and Cleary 61.36%, dare to ask the teacher or other students for 52.30%, and be able to answer the teacher or other student's questions by 56.37%. While the indicators of writing communication skills can write clear and understandable information at 68.20%, the accuracy of the scientific representation of 52.30%, Able to express the data amounting to 56.82, and Able to use Illustrations that can be understood by 50%. The results of the analysis can be concluded that the average percentage of results of oral and written communication skills of students included in the medium category.